Padrão morfo-anatômico de variedades de palma forrageira dos gêneros Opuntia e Nopalea cultivadas no semiárido pernambucano - NORONHA, Claudia Tenório de (2017)
The cactus pear because it is a species adapted to the edaphoclimatic conditions of Semi-arid has been widely used in animal feed. In this context, of cactus pear To present a great genetic diversity of the genus Opuntia e Nopalea, Some varieties are susceptible to pest attack Dactylopius opuntiae (cochonilha-do-carmim) and, as a consequence limits its production, thus the need for research that makes it possible to elucidate because some accesses are susceptible and others are resistant. Therefore, The objective of this study was to distinguish morpho-anatomical patterns related to susceptibility or resistance to carmine cochineal in forage cactus pear varieties cultivated in the semi-arid Brazil. Caulinary traits of seven varieties were analyzed (IPA-100003; IPA-100004; IPA-200008; IPA-200016; IPA-200021; IPA-200149 e IPA-200205), hrough histochemical tests and the production of permanent and semipermanent histological slides, observed in scanning electron microscopy and optical microscope. All varieties studied presented morpho-anatomical, the IPA-100003 has flat epidermis with stomata located above the level of the remaining cells. The IPA-200008 has stomata below the level of the remaining cells. However, both presented non-glandular trichomes in the epidermis, while the others did not. The IPA-200021 presents two types of stomata (tetracytic and hexacylytic). Other characteristics were also recorded as the biometry of palisade parenchyma and storage cells, starch and drusen diameter in the hypodermis and colenchyma. This information will help in decision making in future genetic breeding programs in the face of environmental conditions and will allow new records for the definition of forage cactus pear standards of the genres Opuntia and Nopalea grown in the semi-arid Brazil.